Diaphragmatic Eventration in A Neonate with Acute Respiratory Distress: A Rare Association - Saleem, Muhammad Mudasir (Pakistan Armed Forces Medical Journal, 2025)
Respiratory distress in neonates is mainly secondary to medical causes. Diaphragmatic eventration in neonate leading to respiratory distress is rarely reported in literature. Timely diagnosis and intervention to correct the anomaly has promising outcomes. We present a two days old neonate who presented to pediatric surgery emergency in Combined Military Hospital Lahore, Pakistan in November 2023 with progressive respiratory distress following birth and was diagnosed as having isolated left sided diaphragmatic eventration and his distress settled following surgery.